Study of Eucalyptus pauciflora L. characteristics from Algeria and its impact on the mite affecting honeybees Apis mellifera - Atmani-Merabet, Ghania; Hazmoune, Hicham; Fellah, Sihem; Belkhiri, Abdelmalik (Journal of Agriculture and Applied Biology, 2024)
Essential oils play a crucial role in biological control against parasites threatening the beekeeping stock, both in Algeria and globally. Their appropriate use helps reduce the adverse effects of chemical products on human health and the environment. The purpose of this study is to analyze the components of Eucalyptus pauciflora essential oil grown in Algeria and to evaluate its impact on the marine shrimp Artemia salina and the mite Varroa destructor, while also comparing it to other species of Eucalyptus from the same region namely, Eucalyptus robusta, globulus, sideroxylon, and amygdalina, which have been examine in previous research. Steam distillation of fresh leaves from Eucalyptus pauciflora yielded 0.73% essential oils. This plant contains a total of thirty-nine chemical compounds, among which the most significant are 1,8-cineole (57.45%), β-cymene (5.44%), spathulenol (5.38%), trans-verbenol (4.31%), and α-pinene (3.11%). A lethality test on brine shrimp (BSL) revealed that Eucalyptus pauciflora exhibits toxicity with a median lethal concentration (LC50) of 53.51 ppm. Field trials conducted on hives infested with Varroa destructor showed that the acaricidal effect of Eucalyptus pauciflora is superior to that of amygdalina and sideroxylon species, but inferior to that of globulus and robusta species, all sourced from the same herbarium (Draa Naga) in northeastern Algeria. The results of this research highlight the benefits of Eucalyptus essential oils to be integrated into the formulation of natural acaricides that are environmentally friendly to combat Varroa destructor infestation.